Synthesis and characterization of Jatropha curcas oil based bionanocomposite coating film via green chemistry approach for radiative cooling application / Mohamed Abdul Cader Mohamed Haniffa - Mohamed Abdul Cader , Mohamed Haniffa (2019)
Bionanocomposite is a novel glass of advance material can prepare by green continues phase called matrix and nanomaterials. Non-isocyanate poly(hydroxyl urethane) (NIPHU) is a green chemistry approach which can be used as a continues matrix and to replace the toxic, mutagen, and carcinogenic diisocyantes and their end products from the environment. In this study, 5 membered cyclic carbonate of Jatropha curcas oil (CJCO) and its alkyd resin (CC-AR) were used to synthesis NIPHU with different diamines such as 1,3-diaminopropane (DM) and isophorone diamine (IPDA). CJCO and CC-AR were achieved through carbonation of epoxidized derivatives of JCO in the presence of tetrabutylammonium bromide under desired temperature (T) and pressure (P) of the pressure reactor. The optimization of the T and P were monitored by using FTIR and 1H-NMR spectroscopies. After epoxy conversion, CJCO and CC-AR with carbonate contents of 24.9 and 20.2 wt%, were obtained respectively. Hybrid ZnO nanoparticles were prepared via effective (3-aminopropyl)trimethoxysilane (APTMS) coating of ZnO. Corundum nanoparticles were successfully synthesized by aqueous precipitation and sintering techniques respectively. Acid hydrolysis, TEMPO-oxidation and rapid cooling treatments on cellulose have contributed to the fabrication of TARC-4 with a high number of carboxyl entities and admirable thermal stability. TARC-4 and APTMS-ZnO were characterize by TEM, FTIR, TGA-DTG and XPS respectively. NIPHU films were characterized by spectroscopic techniques, differential scanning calorimetry, and a universal testing machine. Field emission scanning electron microscopy was used to analyze the morphology of the NIPHU film before and after the solvent treatment. The solvent effects were investigated with water, 30% ethanol, methyl ethyl ketone, 10% HCl, 10% NaCl, and 5% NaOH. CJCO was blended with different weight ratios of CC-AR to improve its characteristics. This study shows that the presence of CC-AR in CJCO-based NIPHU can improve the thermo-mechanical and chemical resistance performance of the NIPHU film but degreases the transparency. Acrylic polymer matrix was used to prepare the nanocomposite coating on polyurethane film substrate incorporate of APTMS-ZnO, corundum and commercial SiO2 nanoparticles to investigate their optimum weight ratio for better UV- and IR-absorption. FTIR and UV-visible spectroscopies were used for this purpose. Corundum (2wt%), 6 wt% and 2wt% of SiO2 with 2wt% of APTMS-ZnO embedded 50 m of nanocomposite coatings were prepared respectively and labelled as D50, F50 and E50. The samples, D50 and F50 exhibited 98.77% and 97.60% of UV-and IR-absorption while they lost their visible light transmittance compared to E50. EJCO/NIPHU pre-polymer based hybrid bionanocomposite coatings were prepared incorporate of TARC-4 and APTMS-ZnO to investigate their radiative cooling spectra (UV-and IR-absorption). The structure, radiative spectra and thermo-mechanical properties were analyzed by FTIR, UV-vis spectroscopy, TGA-DTG and pencil hardness tester. The sample NIPUB-10 have exhibited high onset T of 282 C with 8% of char content at 700 C and 392 C of melting T. Moreover, it has shown better absorptions under UV-visible, and mid FTIR-region from 8 m to 13 m compared to other tested samples. Therefore, it is believed that the sample NIPUB-10 exhibit uniform crosslinking and reinforcement network as well as better radiative cooling spectra.